ANALYSIS GENDER AND LANGUAGE IN ONLINE COMMUNICATION (CASE STUDY: TIKTOK AND INSTAGRAM) - Meirandani, Amanda; Ulmasitoh, Cici; Aprilia, Lisa; Elfa M, Yasmin; Nargis, Nargis (VARIABLE RESEARCH JOURNAL, 2025)
This study investigates the influence of gender on language use in online communication, focusing on TikTok and Instagram. Using a qualitative descriptive approach, data were collected from posts and comments to analyze male and female language variations in tone, communication style, and objectives. The findings reveal that women tend to use collaborative and emotional language, fostering connections, while men prefer direct and concise expressions to grab attention. Contextual factors, such as platform dynamics, shape these communication patterns, allowing individuals to challenge traditional gender norms. This study emphasizes the role of gender in shaping digital interactions and highlights the importance of fostering inclusive and diverse representation in online environments.